2021
DOI: 10.3389/fcvm.2021.681484
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Potential of Heart Rate and Hypertension in Multiple Myeloma Patients

Abstract: Background: The prognosis of patients with multiple myeloma (MM) is variable and partly depends on their cardiovascular status. The presence of arrhythmias can lead to worse outcomes. Therefore, this study aimed to evaluate the potential of heart rate (HR) and hypertension in predicating the outcomes of MM patients.Methods: This study retrospectively enrolled patients with MM between January 1, 2010, and December 31, 2018, at the First Affiliated Hospital of Xi'an Jiaotong University. The endpoint was all-caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…11 MM has been reported to be associated with incident atrial fibrillation, 33 and patients with MM with atrial fibrillatio were shown to have an increase in all-cause mortality. 20 These findings are similar to what was reported in our study.…”
Section: Original Researchsupporting
confidence: 93%
See 2 more Smart Citations
“…11 MM has been reported to be associated with incident atrial fibrillation, 33 and patients with MM with atrial fibrillatio were shown to have an increase in all-cause mortality. 20 These findings are similar to what was reported in our study.…”
Section: Original Researchsupporting
confidence: 93%
“…A recent study by Wang et al that showed that patients with MM who had heart rate >100 (though did not specify if they were arrhythmias) reported a higher all-cause mortality in patients who were <75 years old compared with those >75 years. These findings may be because age-related cardiovascular comorbidities attenuated the effect in this age group 20…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Especially in the last ten years, the survival ability of people under 60 has improved significantly. In addition, current studies seem to support the view that renal function [ 16 ], heart rate and hypertension [ 17 ] are also unneglectable factors when evaluating the survival of MM, which were found to be associated with shorter survival. Nevertheless, by contrast, the most important factor related to prognosis is the cytogenetic abnormal status chiefly assessed by fluorescence in situ hybridization [ [18] , [19] , [20] , [21] ], including but not limited to abnormalities of chromosome 1 (1q gains, 1p losses),t (4, 14) (p16, q32), t(14, 16) (q32, q23), deletion of 17p13 and chromosome 22, which are associated with worse prognosis.…”
Section: Prognosis Of MMsupporting
confidence: 71%
“…Many factors have been reported to contribute to the increased incidence of cardiac arrhythmias in patients with MM, such as older age, comorbid cardiovascular conditions, chemotherapeutic agents, and the treatment of coexisting cardiac disease, cardiac amyloidosis, autologous stem cell transplantation (ASCT), and electrolyte abnormalities (6)(7)(8)(9)(10)(11). In our previous work, the QTc interval and heart rate were independently associated with all-cause mortality in patients with MM (12,13). However, the burden of different arrhythmias and the relation between these arrhythmias and prognostic survival in MM patients remain unclear in real-world studies.…”
Section: Introductionmentioning
confidence: 98%